Outcomes of Patients with COVID-19 in a Tertiary Care Hospital of Bangladesh (Bangabandhu Sheikh Mujib Medical College Journal, 2023)
Coronavirus Disease-2019 (COVID-19) has disseminated throughout Bangladesh. This study aimed to provide a detailed account of outcomes of patients with COVID-19 who were hospitalized during 2020-2021 in Bangabandhu Sheikh Mujib Medical College Hospital, Faridpur, Bangladesh. This prospective observational study evaluated outcomes of 500 hospitalized patients with COVID-19. Patients with COVID-19, confirmed by positive Reverse Transcriptase Polyremase Chain Reaction (RT-PCR) reports of nasopharyngeal swab were enrolled in this study. Outcomes of the patients were evaluated by 7-point ordinal scale provided by World Health Organization. Mean age of the respondents was 45.70 (±14.50) years. Out of 500 patients, 331 (66.2%) were male and 169 (33.8%) were female. Common comorbidities were overweight or obesity (191, 38.2%), hypertension (173, 34.6%), diabetes mellitus (163, 32.6%), smoking (90, 18.0%), ischemic heart disease (IHD) (70, 14.0%), asthma (36, 7.2%), chronic obstructive pulmonary disease (COPD) (28, 5.6%), chronic kidney disease (CKD) (18, 3.6%), stroke (12, 2.4%), malignancy (6, 1.2%) and chronic liver disease (CLD) (5, 1.0%). Out of 500 patients, 238 (47.6%) patients had mild disease, 124 (24.8%) patients had moderate disease, 130 (26.0%) patients had severe disease and 8 (1.6%) patients developed critical COVID-19. Among the respondents, 299 (59.8%) patients required low flow oxygen by face mask or nasal prongs, 64 (12.8%) patients required high flow (non-invasive) oxygen therapy, 1(0.2%) patient required non-invasive ventilation (NIV). Duration of hospital stay was significantly (p< 0.05) higher in smokers (12.68±8.672 days) than non-smokers (9.79± 6.007 days). During or soon after discharge, 206 (41.2%) patients could not resumed normal activities of daily life. Only 9 (1.8%) patients died at hospital.Bangabandhu Sheikh Mujib Med. Coll. J. 2023;2(1): 22-28